Desain Model Pembelajaran “Garuda” di Prodi S1 Pendidikan Matematika (suatu implementasi pembelajaran SKA dalam mendukung pelaksanaan KBK Prodi S1 Pendidikan Matematika FKIP Universitas Pekalongan) - Yusuf, Muhammad Ilyas (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
In order to help the matheatics department of teacher’s training and education Faculty of pekalongan University in applying the competence based curiculum the writer designed a teaching method based on SCL, constructivism, and andragogy in May the 1st 2011. This model was named GARUDA which was the softened form of goal setting, andragogy, responsible for the job, understand the material, diciplinary learning and achive learning. The main objective of GARUDA was to make the learners able to master each competence stated in each lecture, so that they can be human investment and not merely human capital.